2017
DOI: 10.1002/jrs.5129
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic CoO–Co3O4 crossover using Raman spectroscopy in magnetic octahedron‐shaped nanocrystals

Abstract: This work describes the effect of the laser power and the exposure time on a sample of octahedron‐shaped nanocrystals of cobalt(II) oxide using Raman spectroscopy. Above a certain value of the laser power and exposure time, CoO rock salt sample evolves clearly to the oxidized Co3O4 normal spinel material because of the energy transfer and consequent local heating induced by the applied laser. The analysis of this thermodynamic CoO–Co3O4 crossover in octahedron‐shaped nanocrystals by means of the Raman spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
177
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(192 citation statements)
references
References 40 publications
15
177
0
Order By: Relevance
“…This is consistent with the irreducible representation of the normal modes showing that only oxygen motions are expected for the A 1g mode . As tetrahedral and octahedral sites share oxygen, oxygen displacements and corresponding restoring forces depend on the nature of both T and M cations, even when these cations are at rest . As a matter of fact, it has been shown that both wavenumber and intensity of the A 1g mode in the Raman spectra depend on the nature of the cations, A or B, and their location on the T and/or M sites .…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…This is consistent with the irreducible representation of the normal modes showing that only oxygen motions are expected for the A 1g mode . As tetrahedral and octahedral sites share oxygen, oxygen displacements and corresponding restoring forces depend on the nature of both T and M cations, even when these cations are at rest . As a matter of fact, it has been shown that both wavenumber and intensity of the A 1g mode in the Raman spectra depend on the nature of the cations, A or B, and their location on the T and/or M sites .…”
Section: Resultssupporting
confidence: 85%
“…With respect to laser‐induced material transformation, the local temperature is definitely a key parameter. In the papers addressing the issue of laser‐induced heating we cite here, local temperatures were actually not determined . This is likely due to technical limitations of spectrometers available.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak located at 206 cm −1 was assigned to the lowest frequency T 2g symmetry species corresponding to the (Co, Al)‐O bending vibration (δ (Co, Al)‐O ) in the CoAl 2 O 4 phase . The broad peaks around 517 and 695 cm −1 were assigned to the F 2g and A 1g modes of the Co 3 O 4 phase . The peaks at 270 and 337 cm −1 were assigned to CoTiO 3 phase, and the peaks at 402 and 387 cm −1 were assigned to Al 2 O 3 phase.…”
Section: Resultsmentioning
confidence: 99%
“…Rivas‐Murias and Salgueirino described a thermodynamic CoOCo 3 O 4 crossover using Raman spectroscopy in magnetic octahedron‐shaped nanocrystals. They found that above a certain value of the laser power and exposure time, CoO rock salt sample evolves clearly to the oxidized Co 3 O 4 normal spinel material because of the energy transfer and consequent local heating induced by the applied laser . Roy et al studied the charge transfer mechanism and adsorptive stance of MB on Au nanocolloids (AuNC).…”
Section: Nannomaterialsmentioning
confidence: 99%